2015
DOI: 10.1021/jp5123568
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Ammonia Transfer Along Two Intramolecular Tunnels in Staphylococcus aureus Glutamine-Dependent Amidotransferase (GatCAB)

Abstract: Most bacteria and all archaea misacylate the tRNAs corresponding to Asn and Gln with Asp and Glu (Asp-tRNAAsn and Glu-tRNAGln). The GatCAB enzyme of most bacteria converts misacylated Glu-tRNAGln to Gln-tRNAGln in order to enable the incorporation of glutamine during protein synthesis. The conversion process involves the intramolecular transfer of ammonia between two spatially separated active sites. This study presents a computational analysis of the two putative intramolecular tunnels that have been suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…D185 forms an edge of Tunnel I, right at the branching point of the two tunnels. The clear importance of this residue for GatCAB activity along with the minimal effects of mutations on structure and interdomain communication provide further support to our computational analyses [30] that revealed that the free energy of migration through Tunnel I is lower than that of Tunnel II. Furthermore, Tunnel I is similar to ammonia exit channels from amidases like that found in fatty acid amide hydrolase [27].…”
Section: Discussionsupporting
confidence: 71%
“…D185 forms an edge of Tunnel I, right at the branching point of the two tunnels. The clear importance of this residue for GatCAB activity along with the minimal effects of mutations on structure and interdomain communication provide further support to our computational analyses [30] that revealed that the free energy of migration through Tunnel I is lower than that of Tunnel II. Furthermore, Tunnel I is similar to ammonia exit channels from amidases like that found in fatty acid amide hydrolase [27].…”
Section: Discussionsupporting
confidence: 71%
“…All EDA calculations were carried out with an in-house FORTRAN90 program to determine the nonbonded interactions (Coulomb and VdW interactions) for all the residues 4850 . The average non-bonded interaction between a particular cytosine derivative and every other residue, ΔE int , is approximated by ΔE int =<ΔE i >, where i represents an individual residue, ΔE i represents the nonbonded interaction (Coulomb or VdW) between residue i and the particular cytosine derivative, and the broken brackets represent averages over the complete production ensemble obtained from the MD simulations.…”
Section: Methodsmentioning
confidence: 99%
“…19,22 A second approach involves the determination of the potential of mean force (PMF). 22,30 Extensive sampling is essential to obtain accurate PMFs since incomplete sampling can result in large errors in the 2 All rights reserved. No reuse allowed without permission.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis has been previously employed for QM/MM and MD simulations to study a number of protein systems. 5,6,30,[78][79][80] …”
mentioning
confidence: 99%